Post-normal times: re-thinking the futures of the EU-Africa relationship - (:unkn) unknown (My University, 2020)
Abstract The nature of the relationship between the European Union (EU) and Africa is in permanent evolution. Historically, the EU mostly dominated the relationship while Africa developed adaptive/reactive strategies. With the establishment of new powers as well as efforts to decolonise the thought and practise of North-South interactions, it is crucial to understand what the future of the relationship could be. The purpose of this paper is to draw lessons from the “Broadening the debate on EU-Africa relations” workshop whose aim was to advance perspectives on EU-Africa relations from the point of view of African scholars. The process consisted of identifying major influential factors in the relationship and assessing what role they played in the past and what role they could play in the future. The results indicate a decline of the importance of EU-dominated factors and the emergence of African agency related factors. We interpret these results as a transformation of this relationship, using the concept “post-normal” to highlight indeterminacy, insolvability and irreversibility as the new context. Implications are discussed regarding the type of research that needs to be developed in order to further investigate this transformation, particularly the meaning of a shifting focus from (normal times) EU-Africa relationship to (post-normal times) Africa-EU relationships.
Keywords: African Research